2010
DOI: 10.1007/s11060-009-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma simultaneously present with adjacent meningioma: case report and review of the literature

Abstract: The simultaneous occurrence of multiple primary intracranial tumors has been reported previously. However, most of these tumors arise after cranial radiotherapy or in association with familial tumor syndromes. Double tumors of different histologies that are unrelated to radiotherapy or genetic disorders are very rare. We present a case of two primary intracranial tumors occurring simultaneously at adjacent sites. Preoperative gadolinium-enhanced magnetic resonance imaging of these tumors revealed a single cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 24 publications
0
59
0
3
Order By: Relevance
“…Nevertheless, molecular features suggest a monoclonal tumor origin [18,19]. The second hypothesis is that the oligodendroglioma and sarcomatous tumor might have coexisted from before the first operation [20][21][22]. However, by following the intensive reexamination of the first radiological images and specimens, we could find no evidence that the sarcomatous components coexisted.…”
Section: Discussionmentioning
confidence: 81%
“…Nevertheless, molecular features suggest a monoclonal tumor origin [18,19]. The second hypothesis is that the oligodendroglioma and sarcomatous tumor might have coexisted from before the first operation [20][21][22]. However, by following the intensive reexamination of the first radiological images and specimens, we could find no evidence that the sarcomatous components coexisted.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, astrocytoma may stimulate growth in adjacent cells by production of common growth factors. Kengo Suzuki et al [20], immunohistochemically showed that platelet-derived growth factor (PDGF) receptors-α and β were overexpressed in glioblastoma multiform meningioma, thereby indicating the oncogenic effects of activated signaling of these receptors. This hypothesis let us speculate that the collision tumor might have been caused by malignant transformation of the reactive gliosis surrounding the meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…Jan Fortuniak et al believe these cases occur incidentally, and the etiology of this phenomenon remains unknown (19). K Suzuki et al in their Immunohistochemical analysis showed that concurrent adjacent double tumors occur because of activation of the signaling pathways of receptor tyrosine kinases (20). According to Tugcu B et al and Black et al (2006) one tumor may secrete a growth factor that initiates growth of another lesion (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…If removal of the tumors is not possible in one session, it is important to decide which tumor should be operated on first (22). YJ Lu et al (2007) suggested that avoiding the complications associated with the transcranial approaches, extended transsphenoidal surgery might be a good alternative choice for approaching suprasellar meningioma and pituitary adenoma simultaneously (20). The ideal approach for treatment of such concomitant tumors is not clear due to lack of adequate experience in the literature (5,11,13,(22)(23)(24)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%